Implementasi Psikoterapi Zikir di Klinik Griya Sehat Syafaat 99: Perspektif Tasawuf, Teologi, dan Psikologi: Perspectives of Sufism, Theology, and Psychology - Asyadily, Muhamad Hasan; Cahyandari, Rinova; Firnanda, Naila Adelia; Widyansyah, Jonathan Aditya (Journal of Sufism and Psychotherapy, 2025)
Psychotherapy involving religious aspects is believed to have a positive impact on improving individual conditions. However, the implementation of zikir therapy can be done differently and will have different impacts. Griya Sehat Syafaat 99 clinic applies zikir therapy that collaborates religious aspects. This article was written with the aim of revealing a description of the implementation of zikir therapy techniques that will be analyzed from sufism, theology, and psychology perspectives. This study is a qualitative phenomenological study involving therapists at the Griya Sehat Syafaat 99 clinic as research respondents. Data were obtained through interviews, observations, and documentation. The results showed that zikir therapy was carried out in five stages, namely the preliminary stage, explanation, examination, implementation, and evaluation. The implementation of zikir psychotherapy from a Sufi perspective incorporates the concept of soul purification (tazkiyatun nafs) through the integration of sharia, haqiqah, and ma'rifah to elevate the levels of the nafs (self). Theologically, zikir guides individuals toward tawhid through dhikr al-qalb, which fosters awareness of Allah’s presence in every utterance, ultimately leading to nafs kamilah (the perfected self). Psychologically, zikir produces a calming effect that is physically manifested through increased alpha brainwave activity. The success of the function of zikir in the context of therapy can be supported by the therapist's mastery of psychological basis, Islamic faith, and Sufism comprehensively in the therapy process.